Membrane-Associated Replication Complex in Arbovirus Infection - Friedman, Robert M. (1972)
Cytoplasmic extracts of chicken embryo fibroblast cells infected with Semliki Forest virus were subjected to isopycnic centrifugation in discontinuous sucrose gradients. Seven distinct bands were usually formed. The four upper bands contained predominantly smooth membranes and the lowest band was enriched in rough endoplasmic reticulum. One fraction (fraction 5), banding at a density of 1.16 g/cm(3), was found to be heavily enriched in pulse-labeled ribonucleic acid (RNA), viral RNA polymerase, and viral RNA forms associated with RNA replication. Thus, fraction 5 evidently contained a membrane-associated viral replication complex of a type previously defined in picornavirus infections. Fraction 5 was also consistently enriched with unique membranous structures previously observed in intact cells as type 1 cytopathic vacuoles (CPV-1). When the CPV-1 in fraction 5 were isolated from cells briefly incubated with (3)H-uridine and (3)H-adenosine prior to cell disruption, a large proportion was found to be labeled by high-resolution autoradiography. Thus, ultrastructural, biochemical, and biological evidence were all consistent with the interpretation that the CPV-1 membranes represent a significant element of the viral replication complex.